Pripovedno izročilo Slovencev v Porabju Pravljice in povedke z zvočnih posnetkov Milka Matičetovega - Matičetov, Milko (Slovenski pravljičarji, 2017)
In this book are published folktales and legends from Porabje / Rába-vidék which were recorded in 1970 by Milko Matičetov on magnetic tapes. The material has been for many decades stored in the archive of the Institute of Slovenian Ethnology ZRC SAZU in Ljubljana. It was only with the help of the experts from Porabje, well-versed in these dialects, that it was possible to publish the recordings.Presented are 238 narrative units, transcribed from tapes in a simplified dialectal transcript. All of the texts are also published in the standard Slovenian language. Two narratives are transcribed in the phonetic dialectological transcription. Added is CD with the recordings of 13 folktales in both varieties of Rába dialect (from Apátistvánfalva and Felsoszölnök district). The introductory section includes studies addressing the development of the narrative culture of Slovenes in Porabje, their language and brief history, as well as a presentation of the storytellers who had narrated these folktales and legends to Milko Matičetov. The folktales have been included in the international database, in accordance with the existing scientific international typology, and are therefore available for further comparative research. This book preserves narrative tradition of Slovenes in Rába-vidék, and is of particular importance to young people, who often no longer speak in the vernacular language.